2008
DOI: 10.1016/j.ajhg.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Innate Immunity in Crohn's Disease and Ulcerative Colitis Identifies Two Susceptibility Loci Harboring CARD9 and IL18RAP

Abstract: The two main phenotypes of inflammatory bowel disease (IBD)--Crohn's disease (CD) and ulcerative colitis (UC)--are chronic intestinal inflammatory disorders with a complex genetic background. Using a three-stage design, we performed a functional candidate-gene analysis of innate immune pathway in IBD. In phase I, we typed 354 SNPs from 85 innate immunity genes in 520 Dutch IBD patients (284 CD, 236 UC) and 808 controls. In phase II, ten autosomal SNPs showing association at p < 0.006 in phase I were replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(207 citation statements)
references
References 56 publications
7
190
0
1
Order By: Relevance
“…Interestingly, SNP rs917997 of the IL18RAP gene, which was associated with disc signal intensity in the present study, was recently shown to be associated with inflammatory bowel disease in 3 independent Dutch cohorts (42). According to the HapMap data, allele A of the rs917997, which was associated with lower average disc signal intensity at the L1-L4 level in our study, perfectly tags the IL1RL1;IL18R1;IL18RAP;SLC9A4 haplotype, which was shown to be associated with both Crohn's disease and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, SNP rs917997 of the IL18RAP gene, which was associated with disc signal intensity in the present study, was recently shown to be associated with inflammatory bowel disease in 3 independent Dutch cohorts (42). According to the HapMap data, allele A of the rs917997, which was associated with lower average disc signal intensity at the L1-L4 level in our study, perfectly tags the IL1RL1;IL18R1;IL18RAP;SLC9A4 haplotype, which was shown to be associated with both Crohn's disease and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 91%
“…It remains to be seen whether the same will hold true for humans. Several loci appear to have opposite effects across related diseases Maier et al 2009), and could represent important checkpoints in the branching pathways that lead to the development of related but distinct diseases (Zhernakova et al 2008). A few GWAS-discovered loci are associated with multiple diseases not previously thought to be related.…”
Section: Gwas and Their Findings-implications For Genetic Architecturementioning
confidence: 99%
“…GWAS of related diseases often reveal an overlapping genetic basis, and the overlaps promise to shed light on disease mechanisms. Several so-called ''autoimmunity'' loci are associated with multiple autoimmune diseases, including the HLA genes of the MHC region, and other genes involved in both innate and adaptive immunity (Maier and Hafler 2008;Zhernakova et al 2008). Among cancers, the 8q24 ''gene desert'' region, has been found to harbor common variants associated with bladder, breast, colon, ovarian, and prostate cancers (reviewed in Ghoussaini et al 2008), whereas most other cancer GWAS discoveries are disease specific (reviewed in Easton and Eeles 2008).…”
Section: The Progress Of Gwas-medical Genetic Discoverymentioning
confidence: 99%
“…The caspase recuitment domain-containing protein 9 (CARD9) plays a role in chronic intestinal inflammation (2,3) and may be an important factor in colorectal cancer progression (4). Its presence in mice is essential for full myeloid activation as well as antifungal response through the immunoreceptor tyrosine-based activation motif (ITAM) domain-containing Dectin transmembrane receptors (5).…”
Section: Introductionmentioning
confidence: 99%